Innovation as A SME Recovery Strategy during The Covid-19 Pandemic in Yogyakarta - Ghofar, Abdul; Effendi, Mohammad Irhas; Kundarto , Muhamad; Amallia, Bunga Alfausta; Adisti, Trisna (RSF Conference Series: Business, Management and Social Sciences, 2021)
The COVID-19 widespread has hurt all economies around the world. In this context, it is hoped that many SMEs will implement a new normal strategy pattern that requires changes in business and management after the pandemic. This research aims to present a multidisciplinary methodological approach to guide SMEs in innovating products for new markets and utilizing limited resources with appropriate strategies. The results showed that. In Yogyakarta, Indonesia, the SME industrial sector prefers a differentiation strategy over cost advantage to drive SME performance. This sector has introduced the practice of using e-commerce which has initially been to reduce production costs to be unique innovations in the market with unique or different products and services offered by companies and improve the performance of SMEs.